PROFILAXIA PRÉ-EXPOSIÇÃO AO HIV E IDENTIFICAÇÃO DE GRUPOS POPULACIONAIS COM RISCO AUMENTADO PARA INFECÇÕES SEXUALMENTE TRANSMISSÍVEIS - PAULA KNOCH MENDONÇA (2024)
Sexually transmitted infections (STI) are among the public health problems of greatest global magnitude due to their wide geographical distribution and difficulties in diagnosis and early access to appropriate treatment. Every day, more than a million people worldwide acquire one of these infections. The significant increase in cases among young people is due to risky sexual behavior combined with a lack of adherence to preventive strategies for STI. The number of people living with the human immunodeficiency virus (PLWHA) worldwide was estimated at 39 million in 2022, of which 1.3 million new infections occurred in that year. Combined prevention strategies to control STI, including HIV pre-exposure prophylaxis (PrEP), have become one of the measures to control the advance of this epidemic in several countries. However, factors such as incipient knowledge and perception can have a direct impact on access to this prophylaxis. The aim of this study was to analyze aspects related to the dispensation of PrEP, the prevalence of STI and social determinants, including the identification of population groups that could benefit from the use of this prophylaxis because they are at increased risk of notifiable STI. To meet the general objective, three methodological sections were carried out: 1 - an ecological study with secondary data on PrEP dispensation and the occurrence of compulsorily notifiable STI (HIV/AIDS, syphilis and viral hepatitis) and socioeconomic data from Brazilian state capitals, from 2018 to 2022. National data on PrEP dispensation and notifications of confirmed cases of HIV/AIDS, acquired/gestational syphilis and viral hepatitis between 2018 and 2022, available on the websites of the Notifiable Diseases Information System (SINAN) and the socioeconomic indicators of the Brazilian Institute of Geography and Statistics (IBGE), year 2010, were considered. The national data is in the public domain and submission to the Ethics Committee was not necessary; 2 - a descriptive, cross- sectional study with secondary data on compulsorily notifiable STI in Campo Grande, MS, between 2014 and 2018. All notifications of confirmed cases of HIV/AIDS, acquired/gestational syphilis and viral hepatitis from the five years prior to the implementation of PrEP in Campo Grande, i.e. 2014 to 2018, were considered and analyzed in this study. The data was made available by the Epidemiological Surveillance Coordination of the Municipal Health Department (SESAU) in 2021. The study was approved by the Research Ethics Committee of the Federal University of Mato Grosso do Sul, via Plataforma Brasil under protocol no. 4.477.496 (CAAE: 39688520.0.0000.0021). Considering that the nominal SINAN database is not in the public domain, a term of commitment for the use of database information was completed; 3 - a cross- sectional descriptive study with primary data on knowledge and perception of PrEP, from the perspective of professionals and users of primary health care (PHC) and specialized care (SC) of the Unified Health System in Campo Grande, MS. The study covered the municipality of Campo Grande, in the state of Mato Grosso do Sul. Primary data was collected through interviews with professionals during face-to-face visits to health services between October 2021 and October 2022. Users of specialized services were also interviewed between October 2021 and April 2022. The study was approved by the Research Ethics Committee of the Federal University of Mato Grosso do Sul, via Plataforma Brasil under opinion no. 4.477.496. The R software was used for the analysis and a 5% significance level was adopted for the three sections of the study. Section 1 showed that the South had the highest STI incidence rates and the North and Northeast had the worst socio-economic indicators. The dispensing of PrEP showed a directly proportional and statistically significant correlation with illiteracy, per capita income, coverage of areas with public waste collection, incidence of syphilis and viral hepatitis. In section 2, syphilis was the most common infection, accounting for 78.5% of all cases. There was a predominance of heterosexual men, aged between 18 and 29 and 40 and 59, brown and with primary education, suggesting that this profile has an increased risk of STIs. In section 3, 514 participants were interviewed, including professionals and users. There was a predominance of male users, aged between 18 and 29, heterosexual, non-white, with higher education and most of whom did not use condoms during sex. There was a higher level of knowledge about PrEP among health professionals and LGBTQIA+ users. Positive perceptions of PrEP were more common among younger users. Raising awareness, training managers, health professionals and users of health services and decentralizing access to PrEP can help expand coverage of access to prophylaxis. Keywords: Pre-Exposure Prophylaxis. Sexually Transmitted Diseases. Epidemiology. Barriers to Access of Health Services. Health Risk Behaviors.